KONSEP ELEMEN DRAMATIK PADA TEATER TRADISONAL MENDU RIAU - Jefrizal, Jefrizal (Jurnal Ilmu Budaya, 2019)
This research was entitled "The Concept of Dramatic Elements in Traditional Tehater Mendu Riau ". The research focused on the dramatic elements. That’re produce the scene and the structure of the play in the show. In Teater Mendu's performing arts at Matan Theater, actors do not use text or texts as a guide to dialogue. Actors only speak of dialogue spontaneously. This is where the emergence of these aesthetic elements, which cannot be reviewed with modern dramaturgy approaches. This study uses Dramaturgy theory with a descriptive qualitative approach. The process of interviewing, observing, documenting is the way to go to find dramatic elemental concepts, Mendu Theater at the Matan Theater Riau. Keywords: Dramatic Element of Tradition Theater, Mendu Riau